From the cradle to the grave: the abandonment of our social contract - Dorling, D (Byline Times Ltd, 2024)
Children are dying younger and growing up shorter, while the elderly’s last years are more painful and desperate than they once were. We have normalised the life of our society falling apart, writes Danny Dorling.